2022
DOI: 10.1088/1755-1315/988/2/022085
|View full text |Cite
|
Sign up to set email alerts
|

Solid Municipal Waste Management for Sustainable Development

Abstract: The article discusses the main directions of improving the management of municipal solid waste in accordance with the requirements of the concept of sustainable development. The concept of “solid municipal waste “is analyzed in its comparison with the concept of “solid household waste”. The problems associated with the functioning of the sphere of solid municipal waste management are emphasized. The tasks of the development of this industry for Russia in the near future are defined. Environmental control of MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Secondly, the municipalities are in charge of local waste management policies when they can employ innovative technologies and resource-saving methods of disposal, e.g. using the waste through reasonable recycling of resources or building a waste-free circular economy [90]. De Jaeger et al [77] indicated also the reversed logic that the political desire for more waste reduction is accompanied by improved managerial expertise or investments in modern and more productive equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the municipalities are in charge of local waste management policies when they can employ innovative technologies and resource-saving methods of disposal, e.g. using the waste through reasonable recycling of resources or building a waste-free circular economy [90]. De Jaeger et al [77] indicated also the reversed logic that the political desire for more waste reduction is accompanied by improved managerial expertise or investments in modern and more productive equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Waste can be defined as all work activities that are not provide added value in the process of transforming inputs into outputs along the value stream mapping. From a lean perspective, all types of waste that exists along the value stream process, which transforms inputs into outputs must be removed in order to increase the value of the product (goods or services) and further increase customer value (Grishaeva et al, 2022). The seven wastes can be grouped into 3 related main categories towards man, machine, and material.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The man category contains the concept of motion, waiting, and over production. The machine category includes over process, meanwhile Material categories include transportation, inventory and defects (Grishaeva et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations